Derivation of human iPS cell lines from monozygotic twins in defined and xeno free conditions - Uhlin, E.; Rönnholm, H.; Day, K.; Kele, M.; Tammimies, K.; Bölte, Sven; Falk, A. (2017)
Human induced pluripotent stem (hiPS) cell lines CTRL-9-II and CTRL-10-I were derived from healthy monozygotic twin donors using non-integrating RNA based Sendai virus reprogramming and cultured in a xeno-free chemically defined condition. The established hiPS cell lines, CTRL-9-II and CTRL-10-I, are karyotypically normal, free from reprogramming vectors, display endogenously expression of pluripotency factors at levels similar to embryonic stem cells. The generated iPS cell lines demonstrate pluripotency by passing bioinformatics assay PluriTest and by embryonic body assay.